Right to Safety and Processing of Personal Data in Covid-19 Pandemic - Tahiraj R; Porro S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The strong limitations to rights of persons, that we all believed to be inviolable shortly before the emergency Covid-19, have raised many questions not only among citizens but also among jurists. The fine line between rights of individuals and rights of community is been countless times bypassed in pandemic management with government measures having urgent nature of application which have seriously affected the labile and difficult balances sought through perennial competitiveness of those rights. Acting in principal interest of community has imposed significant restrictions for individuals to freedom of movement and even to leave their home. Restrictions, equally stringent, have been taken in health sector: let us consider the obligation, in same cases, to undergo an inspection, through a swab, of contagious state. In all of this what role did the laws play on privacy and why, often, it was not necessary to acquire the consent of the individuals interested in implementing some of the procedures for containing the infection? A question which constitute the aim of this study. Methods: Based on a comparative methodology which compares acquis communautaire with Italian legislation, the research sets useful elements for an objective assessment of what happened during Covid-19 pandemic management. Results: The processing of personal data, even if activated without the consent of interested person, does not exclude him from carrying out actions on that data. Conclusion: The citizens can perform a control, even active, on the processing of their data by exercising their rights extended from access to rectification and even their cancellation.